It’s raining. Thieving Government! Climate change and new demand for justice - Meli, Marisa (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2021)
The paper analyzes the new trend on Climate Justice. Particularly, it investigates on legal actions, based on human rights protection and carried against the States, responsible of a weak reaction to the current climate change. Whereas these kind of legal actions are widespread in the world the paper analyzes deeper the European Union experience, starting from the principles recognized in the European Chart of Human Rights